One‐hour post‐load plasma glucose level during the OGTT predicts mortality: observations from the Israel Study of Glucose Intolerance, Obesity and Hypertension. Issue 8 (15th April 2016) - Bergman, M.; Chetrit, A.; Roth, J.; Dankner, R.
Abstract: Aims: The relationship between 1‐ and 2‐h glucose levels following an oral glucose tolerance test (OGTT) and long‐term mortality was evaluated. Methods: Over a 33‐year period, 2138 individuals were followed for all‐cause mortality. Fasting and post‐OGTT glucose parameters categorized the cohort according to baseline glycaemic status. Four categories were established according to 1‐ and 2‐h glucose levels (in mmol/l): group A = 1 h ≤ 8.8 and 2 h < 7.8; group B = 1 h > 8.6 and 2 h < 7.8; group C = 1 h ≤ 8.6 and 2 h = 7.8–11.1 (impaired glucose tolerance); group D = 1 h > 8.6 and 2 h = 7.8–11.1 (impaired glucose tolerance). Individuals with diabetes at baseline were excluded from the cohort. Results: By August 2013, 51% of the study cohort had died. The worst prognosis occurred in group D (73.8% mortality), followed by groups C (67.5%), B and A (57.9% and 41.6%, respectively). When the 2‐h glucose value is 'normal' (< 7.8 mmol/l), the 1‐h glucose value > 8.6 mmol/l is an important predictor of mortality (28% increased risk) compared with group A, controlling for sex, age, smoking, BMI, systolic and diastolic blood pressures. A gradual increased hazard for mortality was seen by study group (hazard ratio = 1.28, 1.60 and 1.76, for groups B, C and D, respectively; group A = reference). Conclusions: A 1‐h glucose value > 8.6 mmol/l predicts mortality even when the 2‐h level is < 7.8 mmol/l. However, when the 2‐h level is in the impaired glucose tolerance range, the hazard for mortality rises significantly independent of the 1‐h value. Individuals at risk for developing diabetes could be identified earlier using the 1‐h threshold value of 8.6 mmol/l, which could avert progression to diabetes and increased mortality.‬ What's new?: A 1‐hour post‐load glucose value > 8.6 mmol/lc predicts mortality even when the 2‐hour level is < 7.8 mmol/l. With the occurrence of IGT, mortality increases significantly independent of 1‐hour level. Individuals at risk for developing diabetes could be identified earlier with the 1‐hour value of 8.6 mmol/l which could avert increased mortality. Further studies are required but it would nonetheless be prudent to include a 1‐hour glucose level during an OGTT to avoid underestimating the severity of glycemic disorders.